Splenic Artery Aneurysm Presenting as Extrahepatic Portal Vein Obstruction: A Case Report - T. P. Elamurugan; S. Suresh Kumar; R. Muthukumarassamy; Vikram Kate (Case Reports in Gastrointestinal Medicine)
Splenic artery aneurysms are the most common visceral aneurysm occuring predominantly in females. They are usually asymptomatic, and the symptomatic presentation includes chronic abdominal pain of varied severity or an acute rupture with hypotension. Splenic artery aneurysm causing extrahepatic portal hypertension is very rare and is due to splenic vein thrombosis that develops secondary to compression by the aneurysm. We report one such rare presentation of splenic artery aneurysms in a pregnant female with the features of EHPVO (variceal bleed, hypersplenism) treated by splenectomy along with excision of the aneurysm.